Role of microbial community in suppressing development of ganoderma in oil palm seedlings - Khunaw, Abdu Rahman; Othman, Radziah; Syed Ali, Nusaibah; Musa, Mohamed Hanafi; Rabara, F. S. (Sciencedomain International, 2017)
Ganoderma boninense is a fungal pathogen causing serious basal stem root (BSR) disease in oil palm. The development of this pathogen can be influenced by soil microbial community. A greenhouse study was conducted to determine the effect of indigenous soil microorganisms on growth of G. boninense inoculated in oil palm seedlings on different soils. Soil samples were collected from three different locations; G. boninense infected soil (S1), non-infected soil (S2) and forest soil (S3). The results showed that sterilized soil without the presence of indigenous microbial population did not suppress the development of G. boninense in oil palm seedlings. The G. 2 boninense inoculated plants grown on sterilized soils had a significantly lower shoot (34.87 g/plant) and root dry weights (9.12 g/plant) as compared to the non-Ganoderma inoculated plants. The highest contents of N (724 mg/plant), P (60 mg/plant), and K (605 mg/plant) were found in seedlings grown in non-infected soil. The lignin content and photosynthesis decreased in G. boninense infected plants while cellulose content varied. The Ganoderma inoculated seedlings showed higher disease severity index and lower shoot yield. Hence, soil devoid of indigenous microorganism negatively affected oil palm seedlings growth due to increased development of G. boninense in the seedlings roots.